"Vitamin D Deficiency and Its Impact on Insulin Resistance in Overweight Children: A Prospective Study" (Comprehensive Journal of Science, 2025)
Vitamin D deficiency is a common global health problem in children, particularly among those who are overweight or obese. Beyond its established role in bone health, vitamin D has been increasingly recognized for its involvement in metabolic regulation, including insulin secretion and insulin sensitivity. Obesity is associated with lower circulating vitamin D levels due to reduced bioavailability, while simultaneously increasing the risk of insulin resistance, a key precursor to type 2 diabetes and metabolic syndrome.This study aims to investigate the relationship between vitamin D deficiency and insulin resistance in overweight children. Specifically, it seeks to determine the prevalence of vitamin D deficiency and to assess its association with markers of insulin resistance, including fasting insulin levels and the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR). The study also explores potential biological mechanisms linking vitamin D status to glucose metabolism and examines whether this association varies according to age, sex, and degree of excess body weight.The central hypothesis is that vitamin D deficiency contributes significantly to the development and severity of insulin resistance in overweight children and that correction of this deficiency may improve insulin sensitivity. Understanding this relationship may help inform early preventive and therapeutic strategies, support clinical decision-making in pediatric care, and guide public health interventions aimed at reducing obesity-related metabolic risk and improving long-term health outcomes in children.